A Study of Encapsulation of Parasitoid Eggs by the Citricola Scale insect, Coccus pseudomagnoliarum (Kuwana) (Hemiptera: Coccomorpha: Coccidae) in Latakia Governorate. (Damascus University Journal of agriculture sciences, 2021)
Insect samples and infested plant parts were collected during April to June 2016 and 2017 from two localities, (Al-Sanobar and Dabba) in Lattakia governorate and they were taken to Biological Control Studies and Research Center (BCSRC) (Faculty of agriculture, Damascus). The citricola scale insect, Coccus pseudomagnoliarum (Kuwana) was able to resist parasitization by the encapsulating parasitoid’s eggs. Maximum encapsulation rate was estimated up to 95.30%, during April 2016 from Daba locality and up to 77.78%, during May 2016 from in Al-sanobar locality. The encapsulation rate (%) showed non-significant negative correlation with mean temperature in Al-sanobar locality. And showed non-significant negative correlation in Al-sanobar locality, and it was significant negative in Daba locality during growing season 2016 and 2017.
Keywords: scale; citricola; encapsulating; temperature; parasitoid’s eggs